Venous Thromboembolism in COVID-19: Towards an Ideal Approach to Thromboprophylaxis, Screening, and Treatment - Aryal, Madan Raj (Curr Cardiol Rep, 2020)
PURPOSE OF REVIEW: Novel coronavirus disease 2019 (COVID-19) has been associated with an increased risk of arterial and venous thromboembolic (VTE) diseases. However, there is a limited amount of data regarding the prevention and management of VTE in severe hospitalized COVID-19 patients. RECENT FINDINGS: In this article, we review currently available clinical data, and mechanisms for COVID-associated coagulopathy, and propose algorithms for screening, prevention (including extended-duration prophylaxis), and treatment of these patients. SUMMARY: Although these recommendations are subject to change given rapidly evolving data, we provide a framework that can guide clinicians in managing thrombotic complications in this challenging condition.